A bibliometric and knowledge-map study of CAR-T cell-related cytokine release syndrome (CRS) from 2012 to 2023 - Huimin Li; Qing Huang; Yuan Zhang (Human Vaccines & Immunotherapeutics)
CAR-T cell therapy has demonstrated efficacy in treating certain hematological malignancies. However, the administration of CAR-T cells is accompanied by the occurrence of adverse events. Among these, cytokine release syndrome (CRS) has garnered significant attention. In this descriptive study, we set the search criteria to retrieve and obtain articles regarding CAR-T cell-related CRS from the Web of Science Core Collection (WoSCC). The bibliometric and knowledge-map analysis of these documents was conducted using Microsoft Excel 2019, GraphPad Prism 8, CtieSpace, and VOSviewer. 6,623 authors from 295 institutions in 49 countries coauthored a total of 1,001 publications. The leading country in this field was the United States. The most productive institution was the University of Pennsylvania. Carl H. June had the most citations, while Daniel W. Lee had the most co-citations. Research hotspots primarily concentrated on the pathogenesis, serum biomarkers, management, and therapeutic drugs of CRS, alongside neurotoxicity. Emerging topics within this discipline encompassed the following: a. Drugs for effective treatment and intervention of CRS; b. Conducting pertinent clinical trials to acquire real-world data; c. Management of toxicity (CRS and neurotoxicity) associated with CAR-T cell therapy; d. The study of BCMA-CAR-T cells in multiple myeloma (MM); e. Optimizing the CAR framework structure to enhance the effectiveness and safety of CAR-T cells. A bibliometric and scientific knowledge-map analysis provided a unique and objective perspective for exploring the field of CAR-T cell-related CRS, and may provide some new clues and valuable references for researchers.